Deep removal impurities in the process of preparing high-purity magnesium by vacuum gasification - Dong Liang; Lipeng Wang; Tingzhuang Ma; Rong Yu; Yang Tian; Baoqiang Xu; Bin Yang (Journal of Magnesium and Alloys)
Magnesium (Mg), as one of the most abundant elements in earth's crust, is the lightest structural metal with extensive applications across various industries. However, the performance of Mg-based products is highly dependent on their impurity levels, and the lack of high-purity Mg, along with efficient purification method, has posed significant challenge to its widespread industrial adoption. This study investigates the impurity behavior in Mg ingots during the vacuum gasification purification process. Through the analysis of binary phase diagrams, iron (Fe)-based foam material was selected for the filtration and purification of Mg vapor in a vacuum tube furnace. A novel approach combining vacuum gasification, vapor purification, and directional condensation is proposed. The effect of filter pore sizes and filtration temperatures on the efficacy of impurity removal was evaluated. Experimental results demonstrate that Fe-based foam with a pore size of 60 ppi, at a filtration temperature of 773 K, effectively removes impurities such as calcium (Ca), potassium (K), sodium (Na), manganese (Mn), silicon (Si), aluminum (Al), and various oxides, sulfides, and chlorides from the vapor phase. Consequently, high-purity Mg with a purity level exceeding 5N3 was obtained in the condensation zone.